Self-stabilizing three-dimensional particle manipulation via a single-transducer acoustic tweezer - Shen, Lu (2023)
This paper investigates the mechanism of self-stabilizing, three-dimensional Mie particle manipulation in water via an acoustic tweezer with a single transducer. A carefully designed acoustic lens is attached to the transducer to form an acoustic vortex, which provides angular momentum on the trapped polymer sphere and leads to a fast-spinning motion. The sphere can find equilibrium positions spontaneously during the manipulation by slightly adjusting its relative position, angular velocity, and spinning axis. The spinning motion greatly enhances the low-pressure recirculation region around the sphere, resulting in a larger pressure induced drag. Simultaneously, the Magnus effect is induced to generate an additional lateral force. The spinning motion of the trapped sphere links the acoustic radiation force and hydrodynamic forces together, so that the sphere can spontaneously achieve new force balance and follow the translational motion of the acoustic tweezer. Non-spherical objects can also be manipulated by this acoustic tweezer.